Persepsi Pemuda Pencari Kerja Terhadap Pekerjaan Sektor Pertanian dan Pilihan Pekerjaan di Desa Cihideung Udik Kecamatan Ciampea, Kabupaten Bogor - Meziriati Hendri; Ekawati Sri Wahyuni (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2013)
This research aim to analyse the perception on agricultural employment and to analyse job preferences among rural youth unemployed in Cihideung Udik village. This research was conducted using quantitative research approach enhanced with qualitative data. The number of respondents were 40 youth job seekers The research result shows that job seekers internal factors, such as, women have some skills and some job experience as well as external factors such as, low socio economic level, less cosmopolitant, and agricultural employment experiences tend to have negative perceptions on agricultural employment. Rural youth unemployed in this village prefer to work in non agricultural sectors, such as in manufacturing sector in area around Bogor and Jakarta.Keyword: perception, unemployment, rural youth, agricultural employment, non agricultural employment